Multimedia selection: Allowing educators to act critically and independently - De Almeida Amorim, Joni; Miskulin, Rosana Giaretta Sguerra [UNESP] (My University, 2011)
In Brazil, important portals like the Portal do Professor, or Teacher's Portal, from the Ministry of Education, offer multimedia products like audios, videos, games, animations, simulations and others with an accompanying teacher's guide. These guides in general suggest ways to prepare the students to use the products while offering indications on how to practice that knowledge after using the products in the classrooom. Despite this, portals with huge repositories that receive new products every week don't present to teachers a solution for a problem: How to select the appropriate products to use in the classroom and how to assess their use after teaching in order to check if the learning was meaningful? In this way, this paper discusses multimedia selection for meaningful learning while considering concept mapping and abstraction classification. The development of multimedia repositories has created both opportunities for easy access to digital content and areas of serious concerns since the misuse of products by teachers may lead to different problems.
Keywords: Abstraction; Concept map; Learning content; Meaningful learning; Multimedia; Concept maps; Learning contents; Abstracting; Animation; Teaching; E-learning